Feasibility of Human Excretory System Module in Biology Learning - Panjaitan, Ruqiah Ganda Putri; Sari, Desti Puspita; Wahyuni, Eko Sri; Shidiq, Galih Albarra (Jurnal Penelitian dan Pembelajaran IPA, 2019)
This study aimed to determine the feasibility of the human excretory system module. The method of this research used was a quantitative descriptive through the instrument of a validation sheet modules which validated by two expert validators. The aspects assessed include the feasibility of the content, language, presentation, and graphics. The results of this research showed the average aspects of feasibility of the content reached the value of 1.00 within the ‘very feasible’ category. The conclusion is the human excretory system module can be useful in teaching biology, especially in human excretory system materials.